The Effectiveness of Learning Media to Introduce Sex Education among Early Childhood (Universitas Negeri Semarang, 2020)
This research aimed to analyze the effectiveness of audio-visual media and serial images toward the improvement of the knowledge of sex education in early childhood. The research method used in this study was Mixed Method. Quantitative approach was used to obtain the effectiveness level of learning video media and serial images. The finding of this research expressed that the implementation of audio-visual media and serial images were still ineffective to be implemented through the learning activity. Those leaning media had the attractiveness, but students cannot optimally receive the message delivered. The effectiveness in this study was marked by the value of Sig. (2-tailed) 0.889 which was bigger than 0,05 (p > 0.05). The result of t-test independent sample testing concluded that the use of learning video and serial images was not effective to improve the knowledge of sex education in early childhood. It means that, there were no differences in the use of learning video and serial image toward the knowledge of early childhood sex education assigned in the value of t-count which was -0.140 with the probability Sig. (2-tailed) 0.889. Meanwhile, the qualitative approach was used to explain the ineffectiveness of learning video media and serial image.